Assisted reproductive techniques in the prevention of mitochondrial diseases - Felipe De Jesús López-Catá; José Sabourín-Divé; Idenia Juana Aguilar-Iraola (Universidad Médica Pinareña, 2020)
Introduction: the mitochondrion is an important organelle that has its own DNA that is sensitive to mutations. These mutations can cause mitochondrial diseases, a heterogeneous group that suggests mitochondrial dysfunction. Objective: to analyze the role of the use of assisted reproductive techniques in the prevention of mitochondrial diseases. Method: a bibliographic review was carried out during May 2019 in SciELO, PubMed and ClinicalKey databases. Twenty articles were consulted using the combination of terms through searching procedures and theoretical methods of analysis-synthesis, induction-deduction and historical-logical methods were applied. Development: part of the information required for the synthesis of mitochondrial components is encoded in the mitochondrial DNA. Mitochondrial diseases have no cure, although they can be avoided by a group of four mitochondrial replacement therapies that include pronuclear, spindle, primary polar body and secondary polar body transfer. However, these techniques can lead to adverse phenomena such as reversal, carryover and incompatibility between nuclear and mitochondrial DNA. The use of these techniques triggers multiple bioethical and social conflicts and a wide diversity of opinions despite their positive results. Conclusions: mitochondrial replacement therapies derived from in-vitro fertilization procedures are available to prevent the transmission of mitochondrial diseases. These therapies have been experimentally supported and are not exempt from adverse biological phenomena. Professionals who advocate for these procedures face bioethical and social challenges regardless of the benefit they may bring to humanity.